Operational Management Assistance at the Jaran Kencak Arts Organization - Emmy Ermawati; Mimin Yatminiwati; Een Yualika Ekmarinda (Trescode Green Organization, 2026)
The purpose of this study is to understand the need for operational management assistance in the art of Jaran Kencak Sri Katon Makmur in Lumajang Regency, East Java, and to formulate strategies that can support the sustainability and development of the traditional art. The methods used included in-depth interviews with the organization's leaders, players, local governments, and the community, which were then confirmed through a Forum Group Discussion (FGD). The data analysis technique was carried out with a descriptive qualitative approach, so that the research results emphasized more on the interpretation of meaning and socio-cultural dynamics. The results of the activity show that all parties have the same view on the importance of operational management assistance. The organization's leaders emphasized the need for more systematic planning, the players wanted a clear schedule and distribution of roles, the government saw great potential in the development of cultural tourism, while the community considered Jaran Kencak as a cultural identity that must be maintained. Confirmation through the FGD strengthens the findings, emphasizing that mentoring is an urgent need to maintain the sustainability of the arts. Art that does not have a management system tends to be stagnant, while art that is supported by structured management is able to survive and thrive. The practical implication of this research is the need for a sustainable mentoring program involving the government, academics, and the community, so that Jaran Kencak art can adapt to the dynamics of the times, expand the reach of the audience, and contribute to regional development through the art and tourism sectors.